The Economic Structure of Hong Kong Administrative Law: Efficiency and Legality of Government Decision-Making Since China’s Resumption - Eric C. Ip (Washington University Global Studies Law Review, 2013)
In contemporary Hong Kong, China’s first special administrative region, administrative law has become ever more influential over government decision-making, notwithstanding the semi-authoritarian political framework of the territory. Contrary to existing scholarship, this Article argues that neither rule-of-law concerns nor misguided judicial adventures satisfactorily explain the evolution of administrative law in this former British colony. Administrative law doctrines are better understood as decisional devices developed to promote “administrative efficiency,” achieved through the reduction of agency costs inflicted by administrative agencies due to imperfect compliance with statutory goals on their political principal—the Hong Kong Legislative Council—to the optimal point where further reduction would yield no benefit to the latter, and the de facto imposition of minimal Kaldor-Hicks efficiency requirements on agency policy outcomes when substantive statutory goals are ambiguous. This Article conjectures that, given the absence of any enabling administrative procedure act, judges’ desire for popular legitimacy and reputation, fear of legislative reversals, and practical needs to conserve their scarce resources explain the underlying design of these doctrines.
Keywords: administrative law; administrative efficiency; special administrative region; Hong Kong; China; Hong Kong Legislative Council; Kaldor-Hicks